2014
DOI: 10.12782/sd.19.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Bivaginogyrus obscurus (Monogenea: Dactylogyridae), a Gill Parasite of Two Cyprinids Pseudorasbora pumila pumila and Pseudorasbora parva, New to Japan

Abstract: The dactylogyrid monogenean Bivaginogyrus obscurus (Gussev, 1955) is redescribed from the gills of two cyprinids, Pseudorasbora pumila pumila Miyadi, 1930 in Nagano Prefecture and P. parva (Temminck and Schlegel, 1846) in Ibaraki Prefecture. These are the first records of this parasite in Japan. Pseudorasbora p. pumila, which is endemic to central Japan, represents a new host record for B. obscurus. This monogenean is the first helminth and the second parasite discovered from wild P. p. pumila.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Remarks. In Japan this monogenean was first described from Pseudorasbora parva and P. pumila Miyadi, 1930 in Lake Kasumigaura, Ibaraki Prefecture and in ponds of Shinonoi, Nagano Prefecture, respectively by Nitta and Nagasawa (2014). The specimens from Nara and Okayama prefectures correspond well with those from Lake Kasumigaura and ponds of Shinonoi.…”
Section: Site Of Infection Gillsmentioning
confidence: 64%
See 3 more Smart Citations
“…Remarks. In Japan this monogenean was first described from Pseudorasbora parva and P. pumila Miyadi, 1930 in Lake Kasumigaura, Ibaraki Prefecture and in ponds of Shinonoi, Nagano Prefecture, respectively by Nitta and Nagasawa (2014). The specimens from Nara and Okayama prefectures correspond well with those from Lake Kasumigaura and ponds of Shinonoi.…”
Section: Site Of Infection Gillsmentioning
confidence: 64%
“…Two of the three monogeneans found in this study, Dactylogyrus squameus and Ancyrocephalus pseudorasborae, were collected from Pseudorasbora parva in the native habitats of this fish in Japan. Thus, as with Bivaginogyrus obscurus (Nitta and Nagasawa 2014), they are considered to be native to Japan. Recently, P. parva has been recorded in Hokkaidō, the Tōhoku District, and Okinawa Prefecture as a domestic alien freshwater fish (Matsuzawa and Senou 2008), and it has also been suggested that some individuals of the species were introduced from the Eurasian continent into several rivers in Japan (Watanabe et al 2000;Yoshigou 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…nebulosus (as I. nebulosus), I. punctatus, N. gyrinus, N. flavus Nepszy (1988) Mexico Ictalurus cf. pricei Rosas-Valdez and León (2005), León et al (2010), Salgado-Maldonado and Quiroz-Martínez 2013Schlegel, 1846) (Cypriniformes: Cyprinidae), respectively (Kamegai 1968, Nitta andNagasawa 2014). Infection by alien monogeneans sometimes poses a high risk for native fish resources (Petrushevski and Shulman 1970;Johnsen and Jensen 1986;Yoshinaga et al 2001;Ogawa 2005Ogawa , 2010Taraschewski 2006), so it is necessary to clarify and monitor the monogenean fauna of this lake.…”
Section: Great Lakesmentioning
confidence: 99%